Batu Khan’s Invasion in the Imagination of French Medieval Authors - Luniak Ye.M. (Золотоордынское обозрение)
Objective: A consideration of the problem of imagining the Mongol-Tatar invasion of Europe (1237–1242) led by Batu Khan in the works of French medieval authors from the thirteenth to the sixteenth centuries. Research materials: Edited sources in Latin, French, and Russian, including works by Giovanni di Pian di Carpine, Alberic de Trois-Fontaines, Matthaeus Parisiensis (Matthew Paris), André Thevet, Benoit Rigaud, and Blaise de Vigenère. Results and novelty of the research: The author considers the evolution of the views of French medieval authors on the problem of the Mongol-Tatar invasion of Europe from the appearance of the first information about the conquerors (Alberic de Trois-Fontaines, Matthaeus Parisiensis) to the formation of a scholarly approach to the study of this issue in the research of historians of the sixteenth century. In particular, the author deals with the ways that information about the Mongol-Tatar invasion of the countries of Eastern Europe penetrated into medieval France. Special attention has been paid to the diplomatic mission of Giovanni di Pian di Carpine (1245–1247) to the Mongol Empire and the participation of the archbishop of Rus’, Petro Akerovich, in the First Council of Lyon (1245). The importance of the Mongol issue for the policy of the French Kingdom in the middle of the thirteenth century is noted too. The attempts of the government of Louis IX to establish contacts with the Mongol Khans are analyzed as well. It is concluded that in subsequent times, a significant influx of slaves from Rus’ into the port cities of Southern France, noted in the fourteenth and fifteenth centuries, might be seen as evidence of the destructive nature of Mongol domination on the Rus’ian lands. Particular attention has been paid to the formation of a scholarly approach in French historical thought of the sixteenth century, when researchers such as André Thevet, Benoit Rigaud, and Blaise de Vigenère tried to recreate the picture of the Mongol-Tatar invasion of Europe in the middle of the thirteenth century based on a critical analysis of the sources, thereby laying the basis for the development of this topic’s historiography in France.